D-TRP(8)-γMSH Prevents the Effects of Endotoxin in Rat Skeletal Muscle Cells through TNFα/NF-KB Signalling Pathway. - Ana Belén Gómez-SanMiguel; María Ángeles Villanúa; Ana Isabel Martín; Asunción López-Calderón (PLoS ONE, 2016)
Sepsis induces anorexia and muscle wasting secondary to an increase in muscle proteolysis. Melanocyte stimulating hormones (MSH) is a family of peptides that have potent anti-inflammatory effects. Melanocortin receptor-3 (MC3-R) has been reported as the predominant anti-inflammatory receptor for melanocortins. The aim of this work was to analyse whether activation of MC3-R, by administration of its agonist D-Trp(8)-γMSH, is able to modify the response of skeletal muscle to inflammation induced by lipopolysaccharide endotoxin (LPS) or TNFα. Adult male rats were injected with 250 μg/kg LPS and/or 500 μg/kg D-Trp(8)-γMSH 17:00 h and at 8:00 h the following day, and euthanized 4 hours afterwards. D-Trp(8)-γMSH decreased LPS-induced anorexia and prevented the stimulatory effect of LPS on hypothalamic IL-1β, COX-2 and CRH as well as on serum ACTH and corticosterone. Serum IGF-I and its expression in liver and gastrocnemius were decreased in rats injected with LPS, but not in those that also received D-Trp(8)-γMSH. However, D-Trp(8)-γMSH was unable to modify the effect of LPS on IGFBP-3. In the gastrocnemius D-Trp(8)-γMSH blocked LPS-induced decrease in pAkt, pmTOR, MHC I and MCH II, as well as the increase in pNF-κB(p65), FoxO1, FoxO3, LC3b, Bnip-3, Gabarap1, atrogin-1, MuRF1 and in LC3a/b lipidation. In L6 myotube cultures, D-Trp(8)-γMSH was able to prevent TNFα-induced increase of NF-κB(p65) phosphorylation and decrease of Akt phosphorylation as well as of IGF-I and MHC I expression. These data suggest that MC3-R activation prevents the effect of endotoxin on skeletal wasting by modifying inflammation, corticosterone and IGF-I responses and also by directly acting on muscle cells through the TNFα/NF-κB(p65) pathway.